Polyaniline-coated nanoparticles of zinc oxide and copper oxide as antifungal agents against Aspergillus parasiticus - Sohail, Younas; Raza, Nadeem; Shakeel, Nasir; Raza, Hina; Manzoor, Suryyia; Yasmin, Ghazala; Iqbal, Amjad; Manzoor, Shamaila; Albaqami, Munirah D.; Mohammad Wabaidur, Saikh (Frontiers in Plant Science, 2022)
Aspergillus parasiticus (A. parasiticus) is known for producing aflatoxins and is a major threat to the food industry. Green synthesis of nanoparticles (NPs) is a cost effective and environment friendly approach. A variety of NPs have been explored as antifungal agents, however their antifungal characteristics need to be further enhanced to compete with traditional fungicides. The present work describes the green synthesis of ZnO and CuO NPs by precipitation method using aqueous leaf extract of Manilkara zapota and their surface modification through polyaniline (PANI). Still there is no published study on the application of PANI coated particles as antifungal agents against A. parasiticus and hence was the focus of this work. The polymer coated NPs were synthesized, characterized and investigated for their antifungal properties against A. parasiticus. Textural and structural characterization of PANI coated and non-coated ZnO and CuO NPs were confirmed through FT-IR, SEM, and XRD techniques. The PANI coated NPs presented higher fungal growth inhibition (%) as compared to the non-coated ones. The maximum inhibition of 77 ± 2% (n=3) was shown by PANI/ZnO NPs at a concentration of 12 mmol L-1 and 72 h of incubation. The non-coated NPs presented a lower inhibition rate with respect to their coated NPs, thus justifying the role of polymeric coating in improving antifungal efficiency.